Legalitas Dan Validitas Visum Et Repertum Yang Dikeluarkan Oleh Dokter Non-Forensik: Perspektif Medikolegal Dalam Pembuktian Tindak Pidana - Yanita, Leli; Fakih, M; Fardiansyah, Ahmad Irzal (Universitas Sang Bumi Ruwa Jurai, 2025)
Visum et repertum is an important piece of evidence in the criminal justice process that serves to bridge the gap between the medical and legal worlds. In practice, the limited number of forensic expert doctors causes the visum et repertum to be issued by general practitioners or doctors who are not forensic experts. This raises a debate regarding the legality and validity of the visum in the process of proving a criminal offense. This paper aims to analyze the legal basis and validity of a visum et repertum made by a doctor who is not a forensic expert from a medicolegal perspective. The method used is the approach of legislation, scientific literature, and case studies. The results of the study show that in order to guarantee fair legal protection for doctors in the practice of national health services. The legality of general practitioners has the authority to make a visum et repertum in accordance with the Criminal Procedure Code and Permenkes, as long as it is carried out based on their professional competence. However, in terms of medicolegal validity, a medical report made by a doctor who is not a forensic expert has the potential to cause weaknesses in evidence if it is not prepared with adequate forensic standards. The novelty of this paper lies in emphasizing the importance of standardizing medical-legal training for non-forensic doctors as a medium-term solution to the limited number of forensic experts in the criminal justice system in Indonesia.]